ASSESSING THE EFFECTIVENESS OF LEARNING MODEL STRATEGIES IN PHYSICAL EDUCATION AT JUNIOR HIGH SCHOOLS IN KUTA BARO, ACEH BESAR - syahrianursaifi; Riski Maulana; Rawi Juwanda; Husaini; Erizal Kurniawan; Musran (Journal of Health and Recreation Physical Education (JHRPE), 2026)
This study aimed to examine the implementation of learning methods and evaluate learning model strategies in Physical Education at junior high schools in Kuta Baro District, Aceh Besar Regency. The research employed a quantitative approach using a descriptive research design. The population and sample consisted of all Physical Education, Sports, and Health (PJOK) teachers working in junior high schools within Kuta Baro District, totaling eight teachers. Data were collected using a structured questionnaire designed to assess the implementation of learning model strategies in Physical Education instruction. The collected data were analyzed using descriptive statistical techniques in the form of percentages. The findings revealed that none of the teachers were classified in the very high category (0.00%) or very low category (0.00%). Six teachers (75.00%) were categorized as having a high level of implementation of learning model strategies, while two teachers (25.00%) fell into the low category. Overall, the evaluation results indicated that the implementation of learning model strategies in Physical Education was classified as high, with an achievement percentage of 75%. These findings suggest that Physical Education teachers in Kuta Baro have generally implemented learning model strategies effectively in the teaching and learning process. Continuous professional development and instructional innovation are recommended to further enhance the quality of Physical Education learning in junior high schools